Advanced-Data Analytics for Understanding Biochemical Pathway Models - Johora, Fatema Tuz; Mia Md Tofayel Gonee Manik; Tasnim, Afia Fairooz; Nilima, Sadia Islam; Hasan, Rakibul (American Journal of Computing and Engineering, 2021)
Purpose: The article delves into the biochemical and metabolic processes, highlighting the importance of data analysis in system biology, drug investigations, illnesses, diagnostics, and therapies, highlighting the necessity of data collection and interpretation. Materials and Methods: The data and sample is collected by analyzing several articles using a simple collective method. Findings: Key pathways for cell respiration include glycolysis, Krebs cycle, and oxidative phosphorylation, which can cause metabolic disorders like diabetes or cancer. Advanced data processing methods and biochemical pathway models have been seen to have the potential to transform biomedical research, advancing our understanding of disease causes, medication development, and individualized medicine. Implications to Theory, Practice and Policy: Challenges such as data complexity, technological limitations, and ethical concerns remain. As technology and methodologies continue to advance, pathway modeling will have more opportunities and become more useful in various sectors, leading to breakthroughs in biology and medicine.